Asymbiotic seed germination and in vitro propagation of Cattleya trianae Linden & Reichb.f. (Orchidaceae) (2017)
Cattleya trianae (Linden & Reichb.f., 1860), Colombian national flower, is in danger of extinction due to the destruction of its natural habitats and excessive collection for horticultural purposes. Therefore, in vitro culture is a tool for the conservation of threatened species. In this study we determined the most suitable culture medium for asimbytic seed germination and in vitro propagation of C. trianae. Initially, mature capsules were collected, the seeds were subsequently disinfected and seeded with the syringe method (Vendrame et al., 2007), to evaluate the effect of five media on the development of C. trianae after 20 weeks. The seedlings were transplanted and acclimated using different substrates. The best percentage (54.2%) of seedling formation after 20 weeks was found in MS + JP medium with significant differences (P <0.05: Tukey HSD). In this research, it is reported that the addition of organic additives to the MS medium improves the efficacy of this, and therefore, allows a greater growth and development of C. trianae under in vitro conditions.